The Impact of Frustration and Anthropomorphism in Chatbots and Digital Assistants’ Adoption - Nunes, Mariana Ferreira (2022)
Dissertation presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Knowledge Management and Business Intelligence